Evaluation of wettabilities and pores in tight oil reservoirs by a new experimental design. (15th September 2019) - Yan, Weichao; Sun, Jianmeng; Golsanami, Naser; Li, Ming; Cui, Likai; Dong, Huaimin; Sun, Yang
Abstract: Understanding different types of pores and their wettability conditions in tight oil reservoirs is a crucial step in evaluating oil accumulation and migration process of these energy resources. Nuclear magnetic resonance (NMR) technique has been widely used in conventional reservoirs to study rock properties including porosity, permeability, pore structures, and wettability. However, the existence of high contents of organic matter and complicated NMR relaxation mechanisms pose considerable challenges on interpreting the NMR results of tight oil reservoirs. In this study, we performed NMR measurements on rock samples under different fluid saturation states and combined the results with imbibition methods as the novel experimental procedure to characterize wettability and pores of tight oil reservoirs. 1D and 2D NMR experiments were first conducted on core samples at four different fluid saturation states including water-saturated state, after-centrifuge state, 80 °C oven-dried state, and 140 °C oven-dried state. Then, we investigated the unmovable hydrogen-bearing matters by monitoring the loss of NMR signal in the four saturation states. In the next step, pores having different wettability conditions were investigated based on the NMR results of oil imbibition and water imbibition experiments. The results showed that while the transverse relaxation behavior of the tight oil rock samples were different from each other, hydrocarbon-wet pores, mix-wet pores and water-wet pores coexisted in these samples. NMR relaxation of oil in hydrocarbon-wet organic pores happened to be the fastest relaxation mechanism compared to other types of pores, and the peak transverse relaxation time was about 0.13 ms. In addition, our experimental results revealed the existence of intermolecular homonuclear dipolar coupling between organic matters and fluids.